Understanding violations of Gricean maxims in preschoolers and adults - Okanda, Mako; Asada, Kosuke; Moriguchi, Yusuke; Itakura, Shoji (Frontiers in Psychology, 2015)
This study used a revised Conversational Violations Test to examine Gricean maxim violations in 4- to 6-year-old Japanese children and adults. Participants’ understanding of the following maxims was assessed: be informative (first maxim of quantity), avoid redundancy (second maxim of quantity), be truthful (maxim of quality), be relevant (maxim of relation), avoid ambiguity (second maxim of manner), and be polite (maxim of politeness). Sensitivity to violations of Gricean maxims increased with age: 4-year-olds’ understanding of maxims was near chance, 5-year-olds understood some maxims (first maxim of quantity and maxims of quality, relation, and manner), and 6-year-olds and adults understood all maxims. Preschoolers acquired the maxim of relation first and had the greatest difficulty understanding the second maxim of quantity. Children and adults differed in their comprehension of the maxim of politeness. The development of the pragmatic understanding of Gricean maxims and implications for the construction of developmental tasks from early childhood to adulthood are discussed.